Ultra-dispersed copper-based nano-enzyme as well as preparation method and application thereof
By self-assembling copper-containing compounds with polyphenol compounds in aqueous solvents to form superdispersed copper-based nanoenzymes, the problem of poor dispersion of existing copper-based nanoenzymes is solved, and long-term stability and excellent antioxidant and inhibition are achieved. Bacterial effect.
Patent Information
- Application Number
- CN202411592459.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing copper-based nanoenzymes have poor dispersion in aqueous solvents and are prone to precipitation, which limits their practical application.
By using the copper-containing compound and polyphenol compounds as a precursor, the superdispersed copper-based nanoenzymes are self-assembled through oxidative coupling in the presence of polymer dispersants and surfactants.
The copper-based nanoenzyme was achieved stably existed in water for at least 14 days, avoiding particle instability and loss of function, improving application effect, and demonstrating excellent antioxidant and antibacterial properties.
Smart Images

Figure CN119456034A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanozymes, and in particular relates to an ultra-dispersed copper-based nanozyme and a preparation method and application thereof. Background Art
[0002] As biocatalysts, natural enzymes catalyze various biochemical reactions in organisms with excellent selectivity and high catalytic efficiency. Therefore, natural enzymes are widely used in biosynthesis, biocatalysis, biosensors and other fields. However, the inherent limitations of natural enzymes, such as low stability, high preparation cost, catalytic efficiency dependent on reaction conditions, and limited reusability, have seriously hindered their industrial application. Nanozymes, as a new generation of artificial mimetic enzymes, can efficiently catalyze enzyme substrates like natural enzymes, showing catalytic efficiency similar to that of natural enzymes, and are more stable than natural enzymes. They can still maintain high catalytic activity in strong acid / base (pH 2-10) or a large temperature range (4-90°C). Compared with natural enzymes, nanozymes have many advantages, including enhanced stability, easy preparation and modification, adjustable catalytic activity and low production cost. Nanozymes have attracted widespread attention in the fields of analytical detection, biomedicine, sterilization, environmental protection, etc.
[0003] Copper ions are one of the essential trace elements for the human body. As a component of many natural enzymes, they play a vital role in the human body. For example, tyrosinase is a copper-containing enzyme that participates in the production of pigments in organisms. Copper-based nanozymes are a class of copper-based nanomaterials with enzyme-like activity. They are mainly developed based on copper or its compounds and have a variety of enzyme-like activities, such as superoxide dismutase-like activity, peroxidase-like activity, oxidase-like activity, etc., which makes them have broad application prospects in many fields.
[0004] CN114306382A discloses a copper-based nanozyme and its preparation method and application. The copper-based nanozyme is prepared by self-assembly of copper salt and phenolic compound to form copper-phenol nanozyme, and then combined with polydopamine nanoparticles. The peroxidase-like activity of the copper-based nanozyme and the photothermal effect of polydopamine under near-infrared light irradiation synergistically resist bacteria and show significant in vitro antibacterial therapeutic effect on common bacterial infections.
[0005] CN116173069A discloses a copper-containing nanosheet nanoenzyme that kills bacteria and promotes wound repair, as well as a preparation method and application thereof. The copper nanosheet is a copper phosphate nanosheet structure chemically coordinated and modified by polyphenols, and needs to be prepared by a long-term high-temperature (160-200°C) hydrothermal reaction. It has a bactericidal effect, can significantly improve the symptoms of difficult wound healing, and promote wound healing.
[0006] CN117772197A discloses a copper-based nanozyme and a preparation method and application thereof. The copper-based nanozyme is prepared by complexing copper ions with palygorskite, has enhanced peroxidase-like activity, can be used as a feasible substitute for natural peroxidase, and is used for the detection of hydrogen peroxide and glucose, and the detection has a wide linear range and a low detection limit.
[0007] However, due to the size effect, the above-mentioned copper-based nanozymes have a large specific surface area and high surface energy, and the interactions such as van der Waals forces and electrostatic attraction between copper-based nanozyme particles are enhanced. Their dispersibility in aqueous solvents is poor, and obvious precipitation often occurs, which also limits the practical application of the above-mentioned copper-based nanozymes.
[0008] Therefore, a copper-based nanozyme that can be stably dispersed in aqueous solvents remains to be developed. Summary of the invention
[0009] The purpose of the present invention is to provide an ultra-dispersed copper-based nanozyme and a preparation method and application thereof in order to overcome the defect of poor dispersibility in aqueous solvents in the prior art.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] The invention provides an ultra-dispersed copper-based nanozyme. The copper-based nanozyme is formed by oxidative coupling self-assembly using a copper-containing compound and a polyphenol compound as precursors in the presence of a polymer dispersant and a surfactant.
[0012] Furthermore, the copper-containing compound includes one or more of copper gluconate, copper sulfate, copper chloride, copper aspartate, copper chlorophyll, copper acetate or copper chlorophyllin, preferably copper sulfate (CuSO4).
[0013] Furthermore, the polyphenol compound includes one or more of tannic acid, epigallocatechin gallate, epigallocatechin galloside, tea polyphenols or catechins, preferably tannic acid (TA).
[0014] Furthermore, the polymer dispersant includes one or more of polyvinyl pyrrolidone, carbomer, carboxymethyl chitosan, hyaluronic acid, polyvinyl alcohol or polyethylene glycol, preferably polyvinyl pyrrolidone (PVP).
[0015] Further, the surfactant includes one or more of sodium dodecyl sulfate, lauryl hydroxysulfobetaine, sodium lauryl polyoxyethylene ether sulfate, sodium lauroyl sarcosinate, sodium lauryl polyoxyethylene ether sulfate, sodium methyl cocoyl taurate, cocamidopropyl betaine, sodium lauroyl amphoacetate or decyl glucoside, preferably sodium dodecyl sulfate (SDS).
[0016] Furthermore, the copper-based nanozyme has an average particle size range of 100-300 nm and has good dispersibility in water.
[0017] Furthermore, the copper-based nanozyme can exist stably in water for at least 14 days, and the average particle size of the copper-based nanozyme remains basically unchanged.
[0018] The present invention also provides a method for preparing an ultra-dispersed copper-based nanozyme, comprising the following steps:
[0019] S1: mixing and stirring the copper-containing compound, the polyphenol compound, the polymer dispersant and the surfactant in water to obtain a uniformly dispersed solution;
[0020] S2: adjusting the pH of the solution to 5-7.4, followed by heating reaction;
[0021] S3: After cooling, the copper-based nanozyme solution is obtained.
[0022] Furthermore, in step S1, the mass ratio of the copper-containing compound, the polyphenol compound, the polymer dispersant and the surfactant is 1:(0.02-0.1):(1-5):(1-5).
[0023] Furthermore, in step S1, the concentration of the copper-containing compound in the solution is 10-50 mg / mL.
[0024] Furthermore, in step S2, the solution used to adjust the pH is a sodium hydroxide solution or an arginine solution.
[0025] Furthermore, in step S2, the temperature of the heating reaction is 30-60°C, and the reaction time is 3-6h.
[0026] The present invention also provides an application of an ultra-dispersed copper-based nanozyme, wherein the ultra-dispersed copper-based nanozyme has good antioxidant properties and can be applied to the antibacterial field.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention provides an ultra-dispersed copper-based nanozyme, which is formed by self-assembly of one or more copper-containing compounds and polyphenol compounds as precursors in the presence of a polymer dispersant or a surfactant. The obtained ultra-dispersed copper-based nanozyme can be stably dispersed in an aqueous solution.
[0029] (2) The ultra-dispersed copper-based nanozyme prepared by the present invention can exist stably in water for more than 2 weeks, proving that it still has excellent dispersion stability in aqueous solvents for a long time, which can prevent its irreversible aggregation, thereby avoiding particle instability and loss of use function, and improving the application effect.
[0030] (3) The preparation method of the ultra-dispersed copper-based nanozyme of the present invention is simple, efficient, fast, green and mild, and has a wide range of materials to choose from. It is suitable for large-scale production of copper-based nanozyme materials and helps to further promote the application field of copper-based nanozymes.
[0031] (4) The ultra-dispersed copper-based nanozyme prepared by the present invention can effectively scavenge 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) free radicals, has excellent antioxidant properties, and can demonstrate its excellent application value in the fields of antibacterial and the like.
[0032] (5) The ultra-dispersed copper-based nanozyme prepared by the present invention has good bactericidal activity against Malassezia, and is expected to treat diseases such as folliculitis and seborrheic dermatitis caused by Malassezia, and has broad application prospects in the fields of skin care and medical health. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the powder X-ray diffraction pattern of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention.
[0034] Figure 2 This is the Fourier transform infrared spectrum of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention.
[0035] Figure 3 This is the photoelectron energy spectrum of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention.
[0036] Figure 4 The photoelectron spectrum of Cu 2p of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention is
[0037] Figure 5 This is a transmission electron microscopy image of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention.
[0038] Figure 6 The dynamic light scattering diagram of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention at different times.
[0039] Figure 7 This is a test of the DPPH clearance rate of the ultra-dispersed copper-based nanozyme of Example 1 of the present invention.
[0040] Figure 8 This is the growth of the corresponding colonies after the super-dispersed copper-based nanozyme of Example 1 of the present invention is co-cultured with Malassezia.
[0041] Fig. 9 The figure shows the samples prepared in Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0043] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0044] Embodiment 1:
[0045] This embodiment provides an ultra-dispersed copper-based nanozyme, which is formed by self-assembly using copper sulfate and tannic acid as precursors in the presence of polyvinyl pyrrolidone and sodium dodecyl sulfate, and is recorded as CuTA / PVP / SDS. The specific preparation method of CuTA / PVP / SDS is as follows:
[0046] Weigh 175 mg of copper sulfate pentahydrate, 5.4 mg of tannic acid, 180.4 mg of polyvinyl pyrrolidone and 180.4 mg of sodium dodecyl sulfate and dissolve them in 10 ml of deionized water, and stir to obtain a uniformly dispersed solution. Use sodium hydroxide solution to adjust the pH of the solution to about 7.4. Then, the reaction solution is stirred at 50 ° C for 3 hours until the reaction is complete. After the reaction is completed, the solution is naturally cooled to room temperature to obtain a CuTA / PVP / SDS ultra-dispersed nanozyme solution. After centrifugation at 10000 rpm, place it in a 60 ° C vacuum drying oven and fully dry it to obtain CuTA / PVP / SDS ultra-dispersed nanozyme powder.
[0047] In this example, the prepared CuTA / PVP / SDS was subjected to the following tests:
[0048] (1) X-ray diffraction characterization: The X-ray diffraction pattern of CuTA / PVP / SDS ultra-dispersed nanozymes is shown in Figure 1 As shown, the sharp peaks in the figure indicate that CuTA / PVP / SDS has a unique crystal structure, which is different from other copper-based materials (such as Cu, Cu2O, CuO and Cu(OH)2).
[0049] (2) Fourier transform infrared spectroscopy characterization: The Fourier transform infrared spectrum of CuTA / PVP / SDS ultra-dispersed copper-based nanozymes is shown in Figure 2. Figure 2 As shown, due to the oxidation of tannic acid and subsequent reaction with Cu 2+ Compared with tannic acid itself, the CuTA nanozyme generated by the coordination is at 3000-3500cm -1 The phenolic hydroxyl stretching vibration peak at 1200 cm -1 The carbon-oxygen stretching vibration peak intensity decreases.
[0050] (3) Photoelectron spectroscopy characterization: The photoelectron spectrum of CuTA / PVP / SDS ultra-dispersed copper-based nanozymes is shown in Figure 3 As shown, the high-resolution photoelectron spectroscopy of Cu 2p Figure 4 The main peaks of Cu 2p 3 / 2 at 935.0 eV and Cu 2p1 / 2 at 955.2 eV are shown.
[0051] (4) Morphological characterization: Transmission electron microscopy images of CuTA / PVP / SDS ultra-dispersed copper-based nanozymes are shown in Figure 2. Figure 5 As shown, the nanozymes are spherical. The small amount of aggregation in the figure may be caused by the drying process during TEM sample preparation.
[0052] (5) Particle size and stability test: Dynamic light scattering diagrams of CuTA / PVP / SDS ultra-dispersed copper-based nanozymes at different times are shown in Figure 2. Figure 6 As shown in the figure, the average particle size of CuTA / PVP / SDS copper-based nanozyme on day 0 was 148.2 nm, and the polydispersity index PDI was 0.018; the average particle size on day 7 was 139.3 nm, and the polydispersity index PDI was 0.078; the average particle size on day 14 was 150.7 nm, and the polydispersity index PDI was 0.162. It can be seen from the results that the particle size and polydispersity index of the prepared CuTA / PVP / SDS ultra-dispersed copper-based nanozyme remain basically unchanged, indicating that the CuTA / PVP / SDS copper-based nanozyme solution has excellent dispersion performance and still has excellent stability in aqueous solvents for up to 14 days.
[0053] (6) DPPH free radical scavenging test:
[0054] Dissolve DPPH in ethanol solution to prepare DPPH-ethanol solution (0.2mM, purple). Take 20μL sample solution and add it to 180μL DPPH-ethanol solution. After reacting at room temperature in the dark for 30 minutes, use an enzyme marker to measure the absorbance at 517nm. Use the DPPH-ethanol solution without sample as the control. The calculation formula of DPPH free radical scavenging ability is as follows:
[0055] DPPH radical scavenging activity (%)=(1-(A1-A2) / A0)×100%.
[0056] Where A1 is the absorbance of sample + DPPH-ethanol solution, A2 is the absorbance of sample + ethanol solution, and A0 is the absorbance of distilled water + DPPH-ethanol solution.
[0057] The DPPH radical scavenging efficiency of CuTA / PVP / SDS ultra-dispersed copper-based nanozymes is as follows Figure 7As shown, the DPPH radical scavenging rate of the ten-fold diluted CuTA / PVP / SDS ultra-dispersed copper-based nanozyme is 69%, which is close to the DPPH radical scavenging rate of the CuTA nanozyme in Comparative Example 1, with no significant difference, indicating that the CuTA / PVP / SDS ultra-dispersed copper-based nanozyme has good antioxidant properties.
[0058] (7) Antibacterial performance test:
[0059] The plate coating method was used to detect the antibacterial effect of the CuTA / PVP / SDS nanozyme prepared in Example 1 on Malassezia. The Malassezia used in the test was Malassezia ATCC14521, and the specific test steps were as follows:
[0060] 1. Medium preparation: Accurately weigh 20g of LB broth, dissolve it in 1000mL of distilled water, heat to dissolve, adjust the pH to between 7.2 and 7.4 with 2mol / L NaOH and 2mol / L HCl, and prepare it into a liquid medium. For solid medium, add 20g of agar powder to the liquid medium and heat to boil. All mediums are sterilized by high pressure.
[0061] 2. Recovery and cultivation of Malassezia furfur: Under sterile conditions, use an inoculation loop to pick up the Malassezia liquid and streak it on a solid culture plate. Place the plate flat in a biochemical incubator and culture it at 28°C for 24 hours. Then pick a single colony and place it in a liquid culture medium. Culture it in a constant temperature shaker at 28°C and 180 r / min for 24 hours for later use.
[0062] 3. Determination of the antibacterial effect of CuTA / PVP / SDS ultra-dispersed copper-based nanozymes on Malassezia: Take the test bacterial solution of Malassezia furfur and dilute it with PBS to about 10 6 -10 7 The nanozyme was diluted to 3 final concentrations of 1 mg / mL, 0.5 mg / mL, and 0.25 mg / mL using the two-fold dilution method. 0.2 mL was added to each test tube. 10 6 CFU / mL of 0.2mL bacterial suspension was used as the control group without adding nanozymes. After all test tubes were placed in a biochemical incubator at 28°C for 24 hours, 0.2mL of the culture in each test tube was taken out and evenly spread on a solid culture plate. The plate was placed flat in a biochemical incubator at 28°C for 24 hours to observe whether colonies were generated. The concentration corresponding to no colony growth was the minimum bactericidal concentration (MBC) of nanozymes against Malassezia.
[0063] The test results are as follows Figure 8As shown, in the control group without the addition of nanozymes, Malassezia filled the culture medium. In contrast, only a very small number of Malassezia colonies grew in the 1 mg / mL CuTA / PVP / SDS nanozyme group, indicating that the MBC of the CuTA / PVP / SDS nanozyme prepared in Example 1 is 1 mg / mL, which has excellent bactericidal properties and has good application prospects in the antibacterial field. It is expected to treat diseases such as folliculitis and seborrheic dermatitis caused by Malassezia.
[0064] Embodiment 2:
[0065] This embodiment provides an ultra-dispersed copper-based nanozyme and a specific preparation method. The difference from Example 1 is that the copper-containing compound of this embodiment is copper gluconate. Other compounds and preparation methods can refer to Example 1.
[0066] Embodiment 3:
[0067] This embodiment provides an ultra-dispersed copper-based nanozyme and a specific preparation method. The difference from Example 1 is that the polyphenol compound of this embodiment is epigallocatechin gallate. Other compounds and preparation methods can refer to Example 1.
[0068] Embodiment 4:
[0069] This embodiment provides different ratios of Example 1, weighing 175 mg of copper sulfate pentahydrate, 5.4 mg of tannic acid, 360.8 mg of polyvinyl pyrrolidone and 360.8 mg of sodium dodecyl sulfate, dissolving in 10 ml of deionized water, and stirring to obtain a uniformly dispersed solution. The pH of the solution was adjusted to about 7.4 with sodium hydroxide solution. Then, the reaction solution was stirred at 50 ° C for 3 hours until the reaction was complete. After the reaction was completed, the solution was naturally cooled to room temperature to obtain a CuTA / PVP / SDS ultra-dispersed nanozyme solution. After centrifugation at 10000 rpm, it was placed in a 60 ° C vacuum drying oven and fully dried to obtain CuTA / PVP / SDS ultra-dispersed nanozyme powder.
[0070] Embodiment 5:
[0071] This embodiment provides different ratios of Example 1, weighing 175 mg of copper sulfate pentahydrate, 10.8 mg of tannic acid, 180.4 mg of polyvinyl pyrrolidone and 180.4 mg of sodium dodecyl sulfate, dissolving in 10 ml of deionized water, and stirring to obtain a uniformly dispersed solution. The pH of the solution was adjusted to about 7.4 with sodium hydroxide solution. Then, the reaction solution was stirred at 50 ° C for 3 hours until the reaction was complete. After the reaction was completed, the solution was naturally cooled to room temperature to obtain a CuTA / PVP / SDS ultra-dispersed nanozyme solution. After centrifugation at 10000 rpm, it was placed in a 60 ° C vacuum drying oven and fully dried to obtain CuTA / PVP / SDS ultra-dispersed nanozyme powder.
[0072] Comparative Example 1:
[0073] This comparative example is a copper-based material obtained without adding a polymer dispersant and a surfactant during the preparation process. The specific preparation process is as follows: 175 mg of copper sulfate pentahydrate and 5.4 mg of tannic acid are weighed and dissolved in 10 ml of deionized water, and the pH of the solution is adjusted to about 7.4 with a sodium hydroxide solution. Then, the reaction solution is stirred at 50°C for 3 hours until the reaction is complete and the reaction product is precipitated. After the reaction is completed, the solution is naturally cooled to room temperature to obtain a precipitated product, CuTA.
[0074] Comparative Example 2:
[0075] This comparative example is a copper-based material obtained by adding only a surfactant during the preparation process. The specific preparation process is: weigh 175 mg of copper sulfate pentahydrate, 5.4 mg of tannic acid, and 180.4 mg of sodium dodecyl sulfate and dissolve them in 10 ml of deionized water, and adjust the pH of the solution to about 7.4 with a sodium hydroxide solution. Then, the reaction solution is stirred at 50°C for 3 hours until the reaction is complete and the reaction product precipitates. After the reaction is completed, the solution is naturally cooled to room temperature to obtain a precipitated product, CuTA / SDS.
[0076] Comparative Example 3:
[0077] This comparative example is a copper-based material obtained by adding only a polymer dispersant during the preparation process. The specific preparation process is: weigh 175 mg of copper sulfate pentahydrate, 5.4 mg of tannic acid, and 180.4 mg of PVP and dissolve them in 10 ml of deionized water, and adjust the pH of the solution to about 7.4 with a sodium hydroxide solution. Then, the reaction solution is stirred at 50°C for 3 hours until the reaction is complete and the reaction product precipitates. After the reaction is completed, the solution is naturally cooled to room temperature to obtain a precipitated product of CuTA / PVP.
[0078] The sample photos of Example 1 and Comparative Examples 1-3 are as follows Fig. 9 As shown, it can be observed that the CuTA of Comparative Example 1, the CuTA / SDS of Comparative Example 2, and the CuTA / PVP of Comparative Example 3 cannot stably exist in aqueous solution and precipitate occurs, while the CuTA / PVP / SDS of Example 1 has good dispersibility in aqueous solution.
[0079] In summary, the present invention provides an ultra-dispersed copper-based nanozyme, which is formed by self-assembly of a copper-containing compound and a polyphenol compound as precursors in the presence of a polymer dispersant or a surfactant. The obtained ultra-dispersed copper-based nanozyme can be stably dispersed in an aqueous solution and can stably exist in water for more than 2 weeks. In addition, the ultra-dispersed copper-based nanozyme prepared by the present invention also exhibits excellent antioxidant and antibacterial properties, can be applied to the antibacterial field, and has good application prospects.
[0080] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A super-dispersed copper-based nanozyme, characterized in that: The copper-based nanozyme is formed by oxidative coupling self-assembly with a copper-containing compound and a polyphenol compound as precursors in the presence of a polymer dispersant and a surfactant.
2. The ultra-dispersed copper-based nanozyme according to claim 1, characterized in that: The copper-containing compound includes one or more of copper gluconate, copper sulfate, copper chloride, copper aspartate, copper chlorophyll, copper acetate or copper chlorophyllin.
3. The ultra-dispersed copper-based nanozyme according to claim 1, characterized in that: The polyphenolic compounds include one or more of tannic acid, epigallocatechin gallate, epigallocatechin galloside, tea polyphenols or catechins.
4. The ultra-dispersed copper-based nanozyme according to claim 1, characterized in that: The polymer dispersant includes one or more of polyvinyl pyrrolidone, carbomer, carboxymethyl chitosan, hyaluronic acid, polyvinyl alcohol or polyethylene glycol.
5. The ultra-dispersed copper-based nanozyme according to claim 1, characterized in that: The surfactant includes one or more of sodium dodecyl sulfate, lauryl hydroxysulfobetaine, sodium lauryl polyoxyethylene ether sulfate, sodium lauroyl sarcosinate, sodium lauryl polyoxyethylene ether sulfate, sodium methyl cocoyl taurate, cocamidopropyl betaine, sodium lauroyl amphoacetate or decyl glucoside.
6. The ultra-dispersed copper-based nanozyme according to claim 1, characterized in that: The average particle size of the copper-based nanozyme ranges from 100 to 300 nm.
7. A method for preparing the ultra-dispersed copper-based nanozyme according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: mixing and stirring the copper-containing compound, the polyphenol compound, the polymer dispersant and the surfactant in water to obtain a uniformly dispersed solution; S2: adjusting the pH of the solution to 5-7.4, followed by heating reaction; S3: After cooling, the copper-based nanozyme solution is obtained.
8. The method for preparing an ultra-dispersed copper-based nanozyme according to claim 7, characterized in that: In step S1, the mass ratio of the copper-containing compound, the polyphenol compound, the polymer dispersant and the surfactant is 1:(0.02-0.1):(1-5):(1-5).
9. The method for preparing an ultra-dispersed copper-based nanozyme according to claim 7, characterized in that: In step S2, the heating reaction temperature is 30-60°C and the reaction time is 3-6h.
10. An application of the ultra-dispersed copper-based nanozyme according to any one of claims 1 to 6, characterized in that: The ultra-dispersed copper-based nanozyme has good antioxidant properties and can be used in the antibacterial field.
Citation Information
Patent Citations
Copper-based nano enzyme as well as preparation method and application thereof
CN117772197A
Cited By
Preparation and application of copper-based nano-enzyme bactericide
CN120477212A